Efecto de la materia orgánica en la sobrevivencia y calidad de planta de regeneración natural de Ocotea aciphylla (Nees) Mez. en vivero, Puerto Almendra, Loreto, Perú – 2023 - Novoa Mafaldo, Glidian Paula (2024)
The objective was to determine the survival and quality of Ocotea aciphylla (Nees) Mez. “canela moena” plants in the nursery in different treatments and controls. The research was carried out in the nursery of the Faculty of Forestry Sciences - UNAP, Puerto Almendra, Loreto. Peru; The effect of 4 types of organic substrates on the survival and quality of Ocotea aciphylla (Nees) Mez. “canela moena” plants was evaluated. The control was considered in the study. The results indicate that treatment t1 (plants planted in 40% chicken manure + 40% decomposed sawdust + 20% sand) surpassed the control t0 (plants planted in 100% natural soil) presenting 90% live plants; In plant quality, treatment 1 also stood out together with the control, which presented REGULAR plant quality at the end of the experiment; similar results were obtained for the test in general.